Eumisetoma pada Toraks dan Abdomen: Suatu Kasus Jarang - Jimy Fran; Istiana Fiatiningsih; Ilhami Romus (Fakultas Kedokteran, Universitas Andalas, 2021)
Mycetoma is a chronic granulomatous infectious disease of the skin, subcutis, fascia and bones caused by bacteria (actinomycetoma) or fungi (eumycetoma) in adults aged 20-40 years old, male to female ratio is 3,7:1 respectively. The clinical finding is a painless, solid and cold subcutaneous node. It has been reported a 43-year-old woman with a painless suppurative lump in her chest, stomach, armpits and legs in the past year. The lump were hypertrophic scars, atrophic scars, nodules and erythematous papules with pustules and sinuses, which excretes exudate greenish-yellow. The patient had a history of working in an oil palm farm. Histopathological examination of hematoxylin-eosin showed suppurative granulomatous inflammation consisting of epitheloid histiocytes, solid lymphocytes and neutrophils, and datia cells. PAS (Periodic acid-Schiff) staining showed positive results. The diagnosis of deep mycosis eumycetoma was confirmed based on physical examination and histopathological examination. Eumycetoma is a rare deep fungal disease. Supporting investigations such as direct microscopy, histopathology with biopsy, and culture are needed to establish the diagnosis. The therapies are antifungal drugs and surgery. Death is possible if the infection occurs in the chest or head cavity.Keywords: deep mycosis, eumycetoma, granules, mycetoma, sinuses